Sosialisasi Aktivitas Kebugaran Jasmani Dalam Meningkatkan Imunitas Tubuh Santri Pesantren Darul Ma'arif Indramayu Pada Masa Adaptasi Kebiasaan Baru (New Normal) - Mochamad Zakky Mubarok; Agi Ginanjar; Dicky Oktora Mudzakir (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
Adaptation Of New Habits (New Normal) Is Compiled And Designed By The Government As One Of The Efforts In Restoring Life And Activities In The Community That Was Stunned By The Covid19 Pandemic. Maintaining Physical Fitness And Increasing Body Immunity Through Physical Activity Can Play An Important Role In Facing The Covid19 Pandemic Situation. The Purpose Of This Community Service Activity Is To Provide Knowledge And Understanding Of The Importance Of Implementing Health Protocols, Maintaining Physical Fitness And Increasing Body Immunity Through Exercise Activities To Students During The New Normal Adaptation Period (New Normal) Covid19. The Implementation Method Used In This Activity Uses Discussion, Socialization And Evaluation. The Target In This Activity Is 50 Students At The Darul Ma'arif Islamic Boarding School, Kaplongan, Indramayu Regency. The Results Of This Activity Have An Impact On The Knowledge And Understanding Of The Students At The Darul Ma'arif Islamic Boarding School, Indramayu Regency About The Importance Of Implementing Health Protocols, Maintaining Physical Fitness And Activities That Can Increase Body Immunity In The Face Of Adaptation To New Habits (New Normal) During The Covid19 Pandemic. 17%.